Polyester glycol and preparation method thereof, polyurethane prepared from polyester glycol and preparation method of polyurethane
By using all-primary hydroxyl polyols and mono-fatty acid capping technology, polyester diols with strict difunctionality were prepared, solving the problem of difficult control of the molecular structure of traditional polyester polyols and achieving improvements in the structural uniformity and mechanical properties of polyurethane.
Patent Information
- Application Number
- CN202510322629.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
The molecular structure of traditional polyester polyols is difficult to control, resulting in insufficient mechanical properties and environmental stability of polyurethane, limiting its application in the field of high-performance materials.
By quantitatively reacting with the first polyol of all primary hydroxyl group and the monofacial fatty acid, the polyester diol with strict difunctionality was prepared by precisely blocking part of the hydroxyl group of the polyol. This polyester diol is good for the esterification reaction, and the polyurethane obtained after esterification has a uniform structure, excellent mechanical properties and environmental stability.
The molecular structural regularity and mechanical properties of polyurethane have been significantly improved, and polyurethane also exhibits good hydrolysis resistance and environmental stability in high temperature and high humidity environments.
Smart Images

Figure CN119841731A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials and polymer chemistry, and in particular to polyester diol and a preparation method thereof, and polyurethane prepared from the polyester diol and a preparation method thereof. Background Art
[0002] Polyurethane (PU) materials have been widely used in many fields such as elastomers, coatings, adhesives and foam materials due to their excellent mechanical properties, wear resistance and chemical stability.
[0003] The inventors have found through a lot of practice that the performance of PU depends largely on the molecular structure of the polyester polyol used. When preparing polyester polyol molecules by traditional methods, the first polyol containing multiple functional groups is usually directly used with a dibasic acid for esterification reaction. For example, the polyester polyol system widely used in industry is a polyester system derived from polyols such as glycerol, sorbitol and xylitol. The traditional method mainly considers cost reduction, and does not consider the control of the molecular structure of the obtained polyester polyol. The polyester polyol with high branching, wide molecular weight distribution and lack of linearity is finally obtained, which cannot meet the requirements of high-performance PU for the regularity of the polyester diol structure. In addition, the branched structure not only increases the complexity of the system and affects the regularity of the polyester polyol, but also affects the microphase separation behavior and mechanical stability of the final PU, thereby limiting its application in the field of high-performance materials. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide a polyester diol and a preparation method thereof, a polyurethane prepared from the polyester diol and a preparation method thereof. The polyester diol of the present invention has strict difunctionality, good molecular regularity, a molecular weight distribution PDI <1.8, good controllability when used for esterification reaction, and the polyurethane obtained after the esterification reaction has a uniform structure and excellent mechanical properties and environmental stability.
[0005] The technical solution of the present invention is achieved by the following methods: A polyester diol, wherein the polyester diol comprises at least one of the following chemical formulas 1-1 to 1-3: Formula 1-1 Formula 1-2 Formula 1-3 Wherein R1 is a saturated or unsaturated hydrocarbon group of C7-C17; R2 is an alkyl group of C2-C14; and n is any integer between 2 and 8.
[0006] The polyester diol of the invention has strict difunctionality, good molecular regularity, molecular weight distribution PDI <1.8, good controllability when used for esterification reaction, and the polyurethane obtained after the esterification reaction has uniform structure and excellent mechanical properties and environmental stability.
[0007] Furthermore, n is 4. When n is 4, the prepared polyester diol has a suitable viscosity and is easy to operate, and when preparing the polyester diol, the required reaction time is suitable and easy to prepare.
[0008] The present invention also provides a method for preparing any of the above-mentioned polyester diols, comprising the following steps: mixing a first polyol and a monobasic fatty acid in a molar ratio of 1:(1-4), adding a first catalyst, evacuating, reacting at a temperature of 180-240° C. for 3-16 hours, then adding a dibasic acid in a molar ratio of (0.9-1.1):1 to the first polyol, and continuing the reaction for 3-16 hours to obtain the polyester diol; The first polyol includes at least one of trimethylolpropane, trimethylolethane, pentaerythritol, and dipentaerythritol; The monobasic fatty acid includes at least one of n-octanoic acid, isooctanoic acid, lauric acid, palmitoleic acid, linoleic acid, stearic acid and vegetable oleic acid.
[0009] The inventors have found through a lot of practice that the controllability of the molecular structure of polyester polyols is closely related to the hydroxyl type (primary hydroxyl and secondary hydroxyl) of the first polyol used as the precursor, and the type and chain length of the acid used.
[0010] On the one hand, the secondary hydroxyl group has a larger steric hindrance effect than the primary hydroxyl group, which limits the approach of the secondary hydroxyl group to the carboxylic acid functional group and affects the efficiency of ester bond formation. Specifically, the esterification rate of the secondary hydroxyl group is about 20%-30% of the esterification rate of the primary hydroxyl group, which will lead to incomplete esterification and residual secondary hydroxyl groups, and then make the molecular weight distribution of the polyester polyol more discrete, causing uncontrollable branching or cross-linking in the subsequent synthesis of PU. In addition, the residual hydroxyl group will further affect the precise control of the NCO:OH molar ratio during the chain extension process, resulting in uneven chain length distribution, disturbing the microphase separation structure of the obtained PU, and further affecting the regular arrangement of the hard segment, reducing the mechanical properties, durability and hydrolysis resistance of the PU, causing the mechanical properties of the PU material to rapidly decline due to accelerated hydrolysis of the ester bond under high temperature and high humidity conditions, making it difficult to meet long-term service requirements.
[0011] On the other hand, during the chain extension process, the type and chain length of the acid also have an important influence on the performance of the final PU. For example, the hard segments formed by short-chain dibasic acids (such as succinic acid and glutaric acid) have strong interactions, which can provide higher hydrogen bond density and rigidity, and significantly improve the tensile strength and wear resistance of PU; while long-chain dibasic acids (such as sebacic acid and dodecane dibasic acid) can introduce greater molecular flexibility, increase the elongation at break of PU, and thus improve flexibility.
[0012] The preparation method of the polyester diol of the present invention uses the first polyol with all primary hydroxyl groups as a raw material, effectively avoids the problem of structural unevenness caused by secondary hydroxyl groups, and adopts a monobasic fatty acid end-capping strategy on this basis. Specifically, the monobasic fatty acid is used to quantitatively react with the first polyol with all primary hydroxyl groups according to the stoichiometric ratio (molar ratio) of 1: (1-4±0.05), and part of the hydroxyl groups of the polyol with all primary hydroxyl groups are accurately capped, so that the prepared polyester diol maintains strict difunctionality, effectively inhibits the branching tendency of the polyol in the esterification reaction, improves the linearity and predictability of the structure of the prepared polyester diol, and provides a more controllable precursor for the subsequent preparation of PU.
[0013] Furthermore, after adding the first catalyst and evacuating the vacuum, when the acid value of the reaction system is lower than 3 mgKOH / g, the dibasic acid can be added to perform an esterification reaction to further extend the chain; after adding the dibasic acid, when the acid value of the reaction system is lower than 3 mgKOH / g and the hydroxyl value of the reaction system reaches 30-80 mgKOH / g, the reaction is considered complete and the reaction can be terminated. If the acid value is too high, the hydroxyl value is too low or the hydroxyl value is too high, the mechanical properties of the polyurethane synthesized from the obtained polyester polyol will be poor.
[0014] Furthermore, the dibasic acid includes at least one of succinic acid, glutaric acid, adipic acid, sebacic acid, undecane dibasic acid, dodecanedioic acid, tridecanedioic acid and tetradecanedioic acid. The dibasic acid is preferred because it is a straight-chain dibasic acid, which can further improve the regularity of the prepared polyester diol molecules, so that the prepared PU has better mechanical properties and environmental stability.
[0015] Further, the first catalyst includes at least one of tetrabutyl titanate, tetraisopropyl titanate, tetraoctyl titanate, titanate ester, tetrabutyl zirconate, tetraisopropyl zirconate, dibutyltin dilaurate and antimony zinc oxide.
[0016] The present invention also provides a polyurethane prepared from any of the above polyester diols. The polyurethane of the present invention has a PDI of less than 2.2, a regular molecular structure, excellent mechanical properties, a strength retention rate of more than 90% after immersion in water at 70°C for 14 days, good hydrolysis resistance, and good environmental stability.
[0017] The present invention also provides a method for preparing any of the above-mentioned polyurethanes, comprising the following steps: The polyester diol and isocyanate are uniformly mixed, wherein the molar ratio of the hydroxyl group in the polyester diol to the NCO group in the isocyanate is 1:(2-2.02), and reacted at 50-90° C. for 1-3 hours to obtain a polyurethane prepolymer; The polyurethane prepolymer and the second polyol are mixed evenly, a second catalyst is added, the mixture is stirred and mixed evenly, and the mixture is reacted at 60-120° C. for 10-16 hours to obtain the polyurethane; The second polyol includes at least one of 1,4-butanediol, ethylene glycol, diethylene glycol, 1,3-propylene glycol and 2-methyl-1,3-propanediol; The molar ratio of the polyurethane prepolymer to the second polyol is 1:(1-1.02).
[0018] When synthesizing polyurethane prepolymers, if the reaction temperature is lower than 50°C, the reaction is extremely slow, which increases the cost. If the reaction temperature is higher than 90°C, violent polymerization will occur. If the reaction time is shorter than 1h, it cannot be fully polymerized. If the reaction time is longer than 3h, the cost will be increased. When synthesizing polyurethane, if the reaction temperature is lower than 60°C, the reaction is extremely slow, which increases the cost. If the reaction temperature is higher than 120°C, the mechanical properties of the obtained product will deteriorate. If the reaction time is shorter than 10h, the performance of the obtained product is poor. If the reaction time is longer than 16h, the cost will be increased. The second polyol of this application adopts a small molecule polyol. The isocyanate of this application preferably adopts Wanhua Chemical MDI100, which is commonly used in industry and has excellent mechanical properties.
[0019] Furthermore, the amount of the second catalyst added is 0.001-0.1wt% of the polyurethane prepolymer. If the amount of the second catalyst added is less than 0.001wt% of the polyurethane prepolymer, the reaction is too slow, and if the amount of the second catalyst added is greater than 0.1wt% of the polyurethane prepolymer, the reaction is too fast and gel is generated.
[0020] Furthermore, the second catalyst includes at least one of an organic tin catalyst, an organic amine catalyst, an organic mercury catalyst and an organic bismuth catalyst.
[0021] Further, the second catalyst includes at least one of dibutyltin dilaurate, dibutyltin dioctoate, organic tin trichloride, triethylenediamine, dimethylaminoethanol, N-methylmorpholine, bis[2-(dimethylamino)ethyl]ether, phenylmercuric acetate, phenylmercuric sulfate, bis(2-ethylhexanoate) bismuth, tri(2-ethylhexanoate) bismuth and bismuth-zinc composite catalyst.
[0022] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The infrared characterization diagram of the polyester diols of the examples and comparative examples of the present invention; Figure 2 The infrared characterization diagrams of the polyurethanes of the embodiments and comparative examples of the present invention; Figure 3 The stress-strain curves of the polyurethanes of Examples 1 to 5 of the present invention and Comparative Examples 1 to 2 are shown; Figure 4 1 is a stress-strain curve diagram of the polyurethane before and after hydrolysis of Example 1 of the present invention; Figure 5 1 is a stress-strain curve diagram of the polyurethane before and after hydrolysis of Example 2 of the present invention; Figure 6 3 is a stress-strain curve diagram of the polyurethane before and after hydrolysis of Example 3 of the present invention; Figure 7 Graphs showing stress-strain curves of the polyurethane of Example 4 of the present invention before and after hydrolysis; Figure 8 Graphs showing stress-strain curves of the polyurethane of Example 5 of the present invention before and after hydrolysis; Fig. 9 The stress-strain curves of the polyurethane of Comparative Example 1 of the present invention before and after hydrolysis. DETAILED DESCRIPTION
[0024] It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present application.
[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0026] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims. In the description of the present application, it should be understood that the terms "first", "second", "third", etc. are only used to distinguish similar objects, and do not have to be used to describe a specific order or sequence, nor can they be understood as indicating or implying relative importance. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0027] In addition, in the description of this application, unless otherwise specified, "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0028] It should be understood that the embodiments of the present application are not limited to the precise structures described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the embodiments of the present application is limited only by the appended claims.
[0029] See also Figure 1 As an embodiment of the present invention, this embodiment provides a polyester diol, wherein the polyester diol comprises at least one of the following chemical formulas 1-1 to 1-3: Formula 1-1 Formula 1-2 Formula 1-3 Wherein R1 is a saturated or unsaturated hydrocarbon group of C7-C17; R2 is an alkyl group of C2-C14; and n is any integer between 2 and 8.
[0030] Furthermore, the n is 4.
[0031] Further, a first polyol and a monobasic fatty acid in a molar ratio of 1:(1-4) are mixed, a first catalyst is added, vacuum is drawn, and the mixture is reacted at a temperature of 180-240° C. for 3-16 hours, and then a dibasic acid in a molar ratio of (0.9-1.1):1 to the first polyol is added, and the reaction is continued for 3-16 hours to obtain the polyester diol; The first polyol includes at least one of trimethylolpropane, trimethylolethane, pentaerythritol, and dipentaerythritol; The monobasic fatty acid includes at least one of n-octanoic acid, isooctanoic acid, lauric acid, palmitoleic acid, linoleic acid, stearic acid and vegetable oleic acid.
[0032] Furthermore, after adding the first catalyst and evacuating the vacuum, when the acid value of the reaction system is lower than 3 mgKOH / g, the dibasic acid can be added to carry out esterification reaction to further extend the chain; after adding the dibasic acid, when the acid value of the reaction system is lower than 3 mgKOH / g and the hydroxyl value of the reaction system reaches 30-80 mgKOH / g, the reaction can be considered complete and the reaction can be terminated.
[0033] Further, the dibasic acid includes at least one of succinic acid, glutaric acid, adipic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid and tetradecanedioic acid.
[0034] Further, the first catalyst includes at least one of tetrabutyl titanate, tetraisopropyl titanate, tetraoctyl titanate, titanate ester, tetrabutyl zirconate, tetraisopropyl zirconate, dibutyltin dilaurate and antimony zinc oxide.
[0035] The present invention also provides a polyurethane prepared from any of the above polyester diols.
[0036] The present invention also provides a method for preparing any of the above-mentioned polyurethanes, comprising the following steps: The polyester diol and isocyanate are uniformly mixed, wherein the molar ratio of the hydroxyl group in the polyester diol to the NCO group in the isocyanate is 1:(2-2.02), and reacted at 50-90° C. for 1-3 hours to obtain a polyurethane prepolymer; The polyurethane prepolymer and the second polyol are mixed evenly, a second catalyst is added, the mixture is stirred and mixed evenly, and the mixture is reacted at 60-120° C. for 10-16 hours to obtain the polyurethane; The second polyol includes at least one of 1,4-butanediol (BDO), ethylene glycol (EG), diethylene glycol (DEG), 1,3-propylene glycol (PDO), and 2-methyl-1,3-propanediol (MPDO); The molar ratio of the polyurethane prepolymer to the second polyol is 1:(1-1.02).
[0037] Furthermore, the added amount of the second catalyst accounts for 0.001-0.1wt% of the polyurethane prepolymer.
[0038] Furthermore, the second catalyst includes at least one of an organic tin catalyst, an organic amine catalyst, an organic mercury catalyst and an organic bismuth catalyst.
[0039] The physical properties and test methods of the embodiments or comparative examples of the present invention are as follows: Polyester diol and polyurethane were analyzed using a Fourier transform infrared spectrometer (ThermoNicolet 6500). The polyurethane film or polyester diol was directly placed on the surface of the ZnSe crystal of the ATR-IR accessory, and the scanning range was 400~4000cm -1 , resolution 4cm -1 , scanning times 32 times; measure the blank background before testing to ensure a smooth baseline; place the sample on the test bench, collect the infrared spectrum, analyze the position and intensity of the functional group absorption peak through software, and compare it with the standard spectrum to confirm the material structure characteristics.
[0040] The molecular weight and distribution characteristics of polyester diols and polyurethanes were determined by Waters 150CV gel permeation chromatography (GPC). Specifically, a GPC instrument equipped with a differential refractive index detector was used. The mobile phase was degassed dimethylformamide (DMF), and the standard sample was polystyrene particles of known molecular weight. The experimental conditions included a flow rate of 0.5 mL / min and a column temperature of 40 ° C. When preparing the sample, weigh about 5-10 mg of dry polyester diol / polyurethane and dissolve it in an appropriate amount of solvent. The concentration was controlled at 0.1%-1% w / w. After ensuring that the system was stable, the test was carried out, and finally the molecular weight (Mw) and polydispersity index (PDI) were calculated by calibration curve and data analysis software.
[0041] The mechanical properties test method of the samples was carried out according to the national standard GB / T528-2009 test method, and the tensile machine used was an Instron 5960 double-column desktop tensile machine.
[0042] The hydrolysis resistance test method of the sample is to cut the polyurethane sample into dumbbell-shaped specimens, soak them in 70°C hot water for two weeks, take them out, and then test their tensile strength, elongation at break and other mechanical properties to evaluate the water resistance of the material.
[0043] Example 1 This embodiment provides a polyester diol, and the preparation method thereof comprises the following steps: 202.79g vegetable oil acid and 96.41g trimethylolpropane TMP were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the mixture was reacted at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, indicating that the reaction had reached the end point. Then 114.42g sebacic acid was added, vacuum was applied, and the mixture was reacted for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g. The hydroxyl value was measured by hydroxyl value titration method to be (45.6±0.3)mgKOH / g, which was close to the theoretical hydroxyl value of 45.3mgKOH / g. The reaction had reached the end point and the structure of the product was in accordance with the expectation, thereby obtaining polyester diol TPA-Polyol, the structure of which is shown in Formula 1-1, and encapsulated. In this embodiment, n=4. In other embodiments, n can also be selected between 2 and 8.
[0044] Take an appropriate amount of the polyester diol TPA-Polyol prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). For the characterization results, please refer to Figure 1 In the spectrum, the characteristic absorption peak of carbonyl (C=O) appears at 1650~1780cm -1 In the range of 3200~3600cm -1 The broad peak absorption observed in the characteristic range further proves that the hydroxyl functional groups are retained at both ends of the polyol molecule. This result confirms the completion of the esterification reaction and the characteristic structure of the polyol.
[0045] The aforementioned polyester diol TPA-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0046] This embodiment also provides a polyurethane, and the preparation method thereof comprises the following steps: 4.8 g of the polyester diol TPA-Polyol prepared in this example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 1.
[0047] Take an appropriate amount of the polyurethane sample 1 prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). Please refer to Figure 2 .
[0048] The polyurethane sample 1 was tested by gel permeation chromatography (GPC), and the film-forming properties and mechanical properties of the polyurethane sample 1 were tested. The test results are shown in Table 2, and the stress-strain curves are shown in Table 2. Figure 3 .
[0049] The polyurethane sample 1 was subjected to a hydrolysis resistance test. The test results are shown in Table 3. The stress-strain curves before and after hydrolysis are shown in Table 3. Figure 4 .
[0050] Example 2 This embodiment provides a polyester diol, and the preparation method thereof comprises the following steps: 103.61g of n-octanoic acid and 96.41g of trimethylolpropane TMP were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the mixture was reacted at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, indicating that the reaction had reached the end point. Then 114.42g of sebacic acid was added, vacuum was applied, and the mixture was reacted for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g. The hydroxyl value was measured by hydroxyl value titration method to be (60.8±0.5)mgKOH / g, which was close to the theoretical hydroxyl value of 61.1mgKOH / g. The reaction had reached the end point and the structure of the product was in accordance with the expectation, thereby obtaining polyester diol TCA-Polyol, the structure of which is shown in Formula 1-1, and encapsulated. In this embodiment, n=4. In other embodiments, n can also be selected between 2 and 8.
[0051] Take an appropriate amount of the polyester diol TCA-Polyol prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). The characterization results are shown in Figure 1 In the spectrum, the characteristic absorption peak of carbonyl (C=O) appears at 1650~1780cm -1 In the range of 3200~3600cm -1 The broad peak absorption observed in the characteristic range further proves that the hydroxyl functional groups are retained at both ends of the polyol molecule. This result confirms the completion of the esterification reaction and the characteristic structure of the polyol.
[0052] The aforementioned polyester diol TCA-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0053] This embodiment also provides a polyurethane, and the preparation method thereof comprises the following steps: 3.8 g of the polyester diol TCA-Polyol prepared in this example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 2.
[0054] Take an appropriate amount of the polyurethane sample 2 prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0055] The polyurethane sample 2 was tested by gel permeation chromatography (GPC), and the film-forming properties and mechanical properties of the polyurethane sample 2 were tested. The test results are shown in Table 2, and the stress-strain curves are shown in Table 2. Figure 3 .
[0056] The polyurethane sample 2 was subjected to a hydrolysis resistance test. The test results are shown in Table 3. The stress-strain curves before and after hydrolysis are shown in Table 3. Figure 5 .
[0057] Example 3 This embodiment provides a polyester diol, and the preparation method thereof comprises the following steps: 202.79g vegetable oil acid and 96.41g trimethylolpropane TMP were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the mixture was reacted at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, indicating that the reaction had reached the end point. Then 66.80g succinic acid was added, vacuum was applied, and the mixture was reacted for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g. The hydroxyl value was measured by hydroxyl value titration method to be (52.0±0.4)mgKOH / g, which was close to the theoretical hydroxyl value of 51.7mgKOH / g. The reaction had reached the end point and the structure of the product was in accordance with the expectation, thereby obtaining polyester diol TPS-Polyol, the structure of which is shown in Formula 1-1, and encapsulated. In this embodiment, n=4. In other embodiments, n can also be selected between 2 and 8.
[0058] Take an appropriate amount of the polyester diol TPS-Polyol prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). The characterization results are shown in Figure 1 In the spectrum, the characteristic absorption peak of carbonyl (C=O) appears at 1650~1780cm -1 In the range of 3200~3600cm -1The broad peak absorption observed in the characteristic range further proves that the hydroxyl functional groups are retained at both ends of the polyol molecule. This result confirms the completion of the esterification reaction and the characteristic structure of the polyol.
[0059] The aforementioned polyester diol TPS-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0060] This embodiment also provides a polyurethane, and the preparation method thereof comprises the following steps: 4.2 g of the polyester diol TPS-Polyol prepared in this example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 3.
[0061] Take an appropriate amount of the polyurethane sample 3 prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0062] The polyurethane sample 3 was tested by gel permeation chromatography (GPC), and the film-forming properties and mechanical properties of the polyurethane sample 3 were tested. The test results are shown in Table 2, and the stress-strain curves are shown in Table 2. Figure 3 .
[0063] The polyurethane sample 3 was subjected to a hydrolysis resistance test. The test results are shown in Table 3. The stress-strain curves before and after hydrolysis are shown in Table 3. Figure 6 .
[0064] Example 4 This embodiment provides a polyester diol, and the preparation method thereof comprises the following steps: 405.58g of vegetable oil acid and 97.73g of pentaerythritol were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the reaction was carried out at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and it was determined that the reaction had reached the end point; then 114.42g of sebacic acid was added, vacuum was applied, and the reaction was carried out for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and the hydroxyl value was measured by hydroxyl value titration method to be (30.1±0.4)mgKOH / g, which was close to the theoretical hydroxyl value of 29.8mgKOH / g, and it was determined that the reaction had reached the end point and the structure of the obtained product was as expected, and polyester diol PPA-Polyol was obtained. Its structure is shown in Formula 1-2, and it was encapsulated, wherein n=4 in this embodiment, and in other embodiments, n can also be selected between 2 and 8.
[0065] Take an appropriate amount of the polyester diol PPA-Polyol prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). The characterization results are shown in Figure 1 In the spectrum, the characteristic absorption peak of carbonyl (C=O) appears at 1650~1780cm -1 In the range of 3200~3600cm -1 The broad peak absorption observed in the characteristic range further proves that the hydroxyl functional groups are retained at both ends of the polyol molecule. This result confirms the completion of the esterification reaction and the characteristic structure of the polyol.
[0066] The aforementioned polyester diol PPA-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0067] This embodiment also provides a polyurethane, and the preparation method thereof comprises the following steps: 8.2 g of the polyester diol PPA-Polyol prepared in this example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then mixed evenly with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 4.
[0068] Take an appropriate amount of the polyurethane sample 4 prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0069] The polyurethane sample 4 was tested by gel permeation chromatography (GPC), and the film-forming properties and mechanical properties of the polyurethane sample 4 were tested. The test results are shown in Table 2, and the stress-strain curves are shown in Table 2. Figure 3 .
[0070] The polyurethane sample 4 was subjected to a hydrolysis resistance test. The test results are shown in Table 3. The stress-strain curves before and after hydrolysis are shown in Table 3. Figure 7 .
[0071] Example 5 This embodiment provides a polyester diol, and the preparation method thereof comprises the following steps: 811.16g of vegetable oil acid and 182.72g of dipentaerythritol were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the reaction was carried out at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and it was determined that the reaction had reached the end point; then 114.42g of sebacic acid was added, vacuum was applied, and the reaction was carried out for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and the hydroxyl value was measured by hydroxyl value titration method to be (16.1±0.2)mgKOH / g, which was close to the theoretical hydroxyl value of 16.4mgKOH / g, and it was determined that the reaction had reached the end point and the structure of the obtained product was in accordance with expectations, and polyester diol DpPA-Polyol was obtained, and its structure was shown in Formula 1-3, and encapsulated, wherein n=4 in this embodiment, and in other embodiments, n can also be selected between 2 and 8.
[0072] Take an appropriate amount of the polyester diol DpPA-Polyol prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). The characterization results are shown in Figure 1 In the spectrum, the characteristic absorption peak of carbonyl (C=O) appears at 1650~1780cm -1 In the range of 3200~3600cm -1 The broad peak absorption observed in the characteristic range further proves that the hydroxyl functional groups are retained at both ends of the polyol molecule. This result confirms the completion of the esterification reaction and the characteristic structure of the polyol.
[0073] The aforementioned polyester diol DpPA-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0074] This embodiment also provides a polyurethane, and the preparation method thereof comprises the following steps: 14.4 g of the polyester diol DpPA-Polyol prepared in this example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 5.
[0075] Take an appropriate amount of the polyurethane sample 5 prepared in this example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0076] The polyurethane sample 5 was tested by gel permeation chromatography (GPC), and the film-forming property and mechanical property of the polyurethane sample 5 were tested. The test results are shown in Table 2, and the stress-strain curve is shown in Table 2. Figure 3 .
[0077] The polyurethane sample 5 was subjected to a hydrolysis resistance test. The test results are shown in Table 3. The stress-strain curves before and after hydrolysis are shown in Table 3. Figure 8 .
[0078] Comparative Example 1 This comparative example provides a polyester diol, and its preparation method comprises the following steps: 202.79g of vegetable oil acid and 66.11g of glycerol were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the reaction was carried out at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and it was determined that the reaction had reached the end point; then 114.42g of sebacic acid was added, vacuum was applied, and the reaction was carried out for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and the hydroxyl value was measured by hydroxyl value titration method to be (49.9±0.9)mgKOH / g, which was close to the theoretical hydroxyl value of 48.7mgKOH / g, and it was determined that the reaction had reached the end point and the obtained product structure was in accordance with expectations, and polyester diol GMP-Polyol was obtained, which was encapsulated, wherein n=4 in this comparative example, and in other embodiments, n can also be selected between 2 and 8.
[0079] Take an appropriate amount of the polyester diol GMP-Polyol prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). For the characterization results, please refer to Figure 1 , confirming the characteristic structure of polyols.
[0080] The aforementioned polyester diol GMP-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0081] This comparative example also provides a polyurethane, and its preparation method comprises the following steps: Take 4.4 g of the polyester diol GMP-Polyol prepared in this comparative example, mix it evenly with 1.4 g of isocyanate MDI100, react at 80° C. for 2 h to obtain a polyurethane prepolymer, then mix the obtained polyurethane prepolymer and 0.32 g of BDO evenly, add 0.06 wt % of an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer, blend in a high-speed mixer, pour into a mold, and mature for 10-16 h to obtain a polyurethane sample 6.
[0082] Take an appropriate amount of the polyurethane sample 6 prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0083] The polyurethane sample 6 was tested by gel permeation chromatography (GPC), and the film-forming properties and mechanical properties of the polyurethane sample 6 were tested. The test results are shown in Table 2, and the stress-strain curves are shown in Table 2. Figure 3 .
[0084] The polyurethane sample 6 was subjected to a hydrolysis resistance test. The test results are shown in Table 3. The stress-strain curves before and after hydrolysis are shown in Table 3. Fig. 9 .
[0085] Comparative Example 2 This comparative example provides a polyester diol, and its preparation method comprises the following steps: 202.79g of vegetable oleic acid and 43.83g of erythritol were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the reaction was carried out at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and it was determined that the reaction had reached the end point; then 57.21g of sebacic acid was added, vacuum was applied, and the reaction was carried out for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and the hydroxyl value was measured by hydroxyl value titration method to be (31.1±1.1)mgKOH / g, which was close to the theoretical hydroxyl value of 30.4mgKOH / g, and it was determined that the reaction had reached the end point and the obtained product structure was in accordance with expectations, and polyester diol EMP-Polyol was obtained, which was encapsulated, wherein n=4 in this comparative example, and in other embodiments, n can also be selected between 2 and 8.
[0086] Take an appropriate amount of the polyester diol EMP-Polyol prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). Please refer to the characterization results. Figure 1 , this result confirms the characteristic structure of polyols.
[0087] The aforementioned polyester diol EMP-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0088] This comparative example also provides a polyurethane, and its preparation method comprises the following steps: 7 g of the polyester diol EMP-Polyol prepared in this comparative example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 7.
[0089] Take an appropriate amount of the polyurethane sample 7 prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0090] The polyurethane sample 7 was tested by gel permeation chromatography (GPC), and the film-forming properties and mechanical properties of the polyurethane sample 7 were tested. The test results are shown in Table 2, and the stress-strain curves are shown in Table 2. Figure 3 .
[0091] The aforementioned polyurethane sample 7 was subjected to a hydrolysis resistance test. Please refer to Table 3 for the test results. The polyurethane sample 7 did not form a film after being immersed in water at 70° C. for two weeks.
[0092] Comparative Example 3 This comparative example provides a polyester diol, and its preparation method comprises the following steps: 608.37g of vegetable oil acid and 109.19g of xylitol were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the reaction was carried out at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and it was determined that the reaction had reached the end point; then 114.42g of sebacic acid was added, vacuum was applied, and the reaction was carried out for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and the hydroxyl value was measured by hydroxyl value titration method to be (21.5±0.4)mgKOH / g, which was close to the theoretical hydroxyl value of 22.1mgKOH / g, and it was determined that the reaction had reached the end point and the obtained product structure was in accordance with expectations, and the polyester diol XMP-Polyol was obtained, and encapsulated, wherein n=4 in this comparative example, and in other embodiments, n can also be selected between 2 and 8.
[0093] Take an appropriate amount of the polyester diol XMP-Polyol prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). For the characterization results, please refer to Figure 1 , this result confirms the characteristic structure of polyols.
[0094] The aforementioned polyester diol XMP-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0095] This comparative example also provides a polyurethane, and its preparation method comprises the following steps: 9.8 g of the polyester diol XMP-Polyol prepared in this comparative example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 8.
[0096] Take an appropriate amount of the polyurethane sample 8 prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0097] The aforementioned polyurethane sample 8 was tested by gel permeation chromatography GPC, and the film-forming property and mechanical property of the aforementioned polyurethane sample 8 were tested. Please refer to Table 2 for the test results.
[0098] Comparative Example 4 This comparative example provides a polyester diol, and its preparation method comprises the following steps: 811.16g of vegetable oleic acid and 130.78g of sorbitol were mixed evenly, tetrabutyl titanate was added, vacuum was applied, and the mixture was reacted at a temperature of 180-240°C for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g, and it was determined that the reaction had reached the end point. Then 114.42g of sebacic acid was added, vacuum was applied, and the mixture was reacted for 6h. The acid value was measured by acid value titration method to be less than 3mgKOH / g. The hydroxyl value was measured by hydroxyl value titration method to be (16.7±0.6)mgKOH / g, which was close to the theoretical hydroxyl value of 17.3mgKOH / g. It was determined that the reaction had reached the end point and the structure of the obtained product was in accordance with expectations, and polyester diol SMP-Polyol was obtained, which was encapsulated. In this comparative example, n=4. In other embodiments, n can also be selected between 2 and 8.
[0099] Take an appropriate amount of the polyester diol SMP-Polyol prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). The characterization results are shown in Figure 1 , this result confirms the characteristic structure of polyols.
[0100] The aforementioned polyester diol SMP-Polyol was tested by GPC. Please refer to Table 1 for the test results.
[0101] This comparative example also provides a polyurethane, and its preparation method comprises the following steps: 12.4 g of the polyester diol SMP-Polyol prepared in this comparative example was mixed evenly with 1.4 g of isocyanate MDI100, and reacted at 80° C. for 2 h to obtain a polyurethane prepolymer. The obtained polyurethane prepolymer was then evenly mixed with 0.32 g of BDO, and an organic tin catalyst accounting for 0.06 wt % of the polyurethane prepolymer was added, blended in a high-speed mixer, poured into a mold, and aged for 10-16 h to obtain a polyurethane sample 9.
[0102] Take an appropriate amount of the polyurethane sample 9 prepared in this comparative example and characterize it by Fourier transform infrared spectrometer (FTIR). Figure 2 .
[0103] The aforementioned polyurethane sample 9 was tested by gel permeation chromatography GPC, and the film-forming property and mechanical property of the aforementioned polyurethane sample 9 were tested. Please refer to Table 2 for the test results.
[0104] Table 1 GPC test results of polyester polyols of Examples 1 to 5 and Comparative Examples 1 to 4
[0105] Table 2 GPC test, film forming performance test and mechanical properties test results of samples 1 to 9
[0106] Table 3 Hydrolysis resistance test results of samples 1 to 7 (immersed in water at 70°C for two weeks)
[0107] Combining the molecular weight data in Table 1 and Figure 1 The FTIR data analysis can verify the successful synthesis of 9 polyester diols; combined with the molecular weight data in Table 2 and Figure 2 The FTIR data analysis can verify the successful synthesis of 9 PUs.
[0108] The present invention reasonably selects a combination of a capped monoacid and a chain-extending diacid, effectively regulating the rigid-flexible balance of the PU material, the PDI of the polyester diols of Examples 1 to 5 is less than 1.8, and the controllability and microphase separation stability of the prepared polyurethane structure are improved. The polyurethane prepared by using the polyester diols of Examples 1 to 5 of the present invention has a PDI of less than 2.2, regular molecules, excellent reaction controllability, good processing applicability, a breaking stress of at least 3.2 MPa, which is more than 60% higher than that of the secondary hydroxyl system, an elongation at break of at least 229.4%, and a toughness of at least 3.5 MJ / m 3 , and after the hydrolysis resistance test, the mechanical properties of polyurethane can decrease by no more than 10% after being immersed in water at 70°C for 14 days.
[0109] The polyester diols of Comparative Examples 1 to 4 are all prepared using polyols containing secondary hydroxyl groups, and their PDI is ≥ 2.25, which is generally greater than the PDI of the polyester diols of the embodiments of the present application. The polyurethanes prepared using the polyester diols of Comparative Examples 1 to 4 have a PDI>4 and poor film-forming properties. Only the polyurethanes prepared using the polyester diols of Comparative Examples 1 to 2 can form films, but their breaking stress, elongation at break and toughness are generally inferior to those of the polyurethanes of the embodiments of the present application. After the hydrolysis resistance test, only the polyurethane of Comparative Example 1 can form films, but its mechanical properties decrease by more than 50%, making it difficult to meet the requirements of long-term service.
[0110] It can be seen that the PDI of PU prepared from polyester diols synthesized from all-primary hydroxyl polyols is significantly lower than that of PU synthesized from a polyol system containing secondary hydroxyl groups.
[0111] By comparing polyurethane samples 1-3 and 6, it can be seen that under the same hydroxyl functionality conditions, the polyester diol formed by monobasic fatty acid end-capping and dibasic acid chain extension, the primary hydroxyl content in the precursor polyol small molecule directly determines the molecular structure and mechanical properties of the final PU. With the increase of primary hydroxyl content, the polymer regularity of the obtained PU is enhanced and the mechanical properties are significantly improved. However, the steric hindrance effect of secondary hydroxyl makes its esterification activity much lower than that of primary hydroxyl (about 20%-30%), resulting in incomplete esterification reaction and the formation of unreacted hydroxyl residues. These residual hydroxyl groups will cause uncontrollable branching or cross-linking during the PU synthesis process, increase the PDI of PU>4, thereby destroying the microphase separation structure of PU, causing disordered arrangement of hard segments, and ultimately reducing the mechanical properties of PU.
[0112] Further comparison of polyurethane samples 1 and 2 shows that as the alkyl chain segment of the end-capped monoacid shortens, the fracture stress of the prepared PU increases, which is attributed to the higher regularity of the short-chain alkyl end-capping structure, which makes the hard segment micro-area arrangement of PU more orderly, thereby enhancing the hydrogen bonding effect and increasing the fracture stress of PU. However, as the alkyl chain segment of the end-capped monoacid shortens, the fracture strain of PU decreases, which is because the long-chain alkyl end-capping provides greater molecular flexibility, making PU easier to deform during stretching.
[0113] Further comparison of polyurethane samples 1 and 3 shows that the shorter the dibasic acid segment used in the polyester chain extension process, the higher the final PU fracture stress. This is because the shorter dibasic acid segment shortens the ester bond distance, increases the hard segment density, and enhances the rigidity, thereby improving the tensile strength of PU, but also reduces the flexibility of PU, causing its fracture strain to decrease.
[0114] Further comparison of polyurethane samples 4 and 7 shows that when the number of hydroxyl groups of the polyol small molecules is the same, when all hydroxyl groups are primary hydroxyl groups (sample 4), its mechanical properties are significantly better than those of sample 7 in which some hydroxyl groups are secondary hydroxyl groups.
[0115] Further comparison of polyurethane samples 5 and 9 shows that dipentaerythritol and sorbitol, both of which have 6 hydroxyl groups, are used as precursors to prepare polyester diols and their PU products. The sorbitol system (sample 9) is no longer able to form a film, while the dipentaerythritol system (sample 5) still has good mechanical properties. This further verifies the decisive role of the primary hydroxyl content of the small polyol molecules used to prepare polyester diols on the structural regularity and mechanical properties of the final prepared TPU.
[0116] In summary, the content of primary hydroxyl groups in polyester diol precursors directly determines the structure and mechanical properties of PU. With the increase of primary hydroxyl content, the resulting PU has higher molecular regularity and better mechanical properties. In addition, the structure of the end-capped monoacid and diacid also significantly affects the performance of PU. Short-chain end-capping enhances rigidity, while long-chain end-capping improves flexibility; short-chain diacids increase tensile strength, while long-chain diacids increase fracture strain. The above research results provide a new strategy for the molecular design of high-performance PU materials.
[0117] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A polyester diol, characterized in that The polyester diol includes at least one of the following chemical formulas 1-1 to 1-3: Formula 1-1 Formula 1-2 Formula 1-3 Wherein, R1 is a saturated or unsaturated hydrocarbon group of C7-C17; R2 is an alkyl group of C2-C14; and n is any integer between 2 and 8.
2. The polyester diol according to claim 1, characterized in that The n is 4.
3. A method for preparing a polyester diol as claimed in any one of claims 1 to 2, characterized in that: The method comprises the following steps: mixing a first polyol and a monobasic fatty acid in a molar ratio of 1:(1-4), adding a first catalyst, evacuating, reacting at a temperature of 180-240° C. for 3-16 hours, then adding a dibasic acid in a molar ratio of (0.9-1.1):1 to the first polyol, and continuing the reaction for 3-16 hours to obtain the polyester diol; The first polyol includes at least one of trimethylolpropane, trimethylolethane, pentaerythritol, and dipentaerythritol; The monobasic fatty acid includes at least one of n-octanoic acid, isooctanoic acid, lauric acid, palmitoleic acid, linoleic acid, stearic acid and vegetable oleic acid.
4. The method for preparing polyester diol according to claim 3, characterized in that: After adding the first catalyst and evacuating the system, when the acid value of the reaction system is lower than 3 mgKOH / g, the dibasic acid can be added; after adding the dibasic acid, when the acid value of the reaction system is lower than 3 mgKOH / g and the hydroxyl value of the reaction system reaches 30-80 mgKOH / g, the reaction is terminated.
5. The method for preparing polyester diol according to claim 3, characterized in that: The dibasic acid includes at least one of succinic acid, glutaric acid, adipic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid and tetradecanedioic acid.
6. The method for preparing polyester diol according to claim 3, characterized in that: The first catalyst includes at least one of tetrabutyl titanate, tetraisopropyl titanate, tetraoctyl titanate, titanate ester, tetrabutyl zirconate, tetraisopropyl zirconate, dibutyltin dilaurate and antimony zinc oxide.
7. A polyurethane, characterized in that Prepared from the polyester diol as described in any one of claims 1 to 2.
8. A method for preparing polyurethane according to claim 7, characterized in that: The following steps are involved: The polyester diol and isocyanate are uniformly mixed, wherein the molar ratio of the hydroxyl group in the polyester diol to the NCO group in the isocyanate is 1:(2-2.02), and reacted at 50-90° C. for 1-3 hours to obtain a polyurethane prepolymer; The polyurethane prepolymer and the second polyol are mixed evenly, a second catalyst is added, the mixture is stirred and mixed evenly, and the mixture is reacted at 60-120° C. for 10-16 hours to obtain the polyurethane; The second polyol includes at least one of 1,4-butanediol, ethylene glycol, diethylene glycol, 1,3-propylene glycol and 2-methyl-1,3-propanediol; The molar ratio of the polyurethane prepolymer to the second polyol is 1:(1-1.02).
9. The method for preparing polyurethane according to claim 8, characterized in that: The added amount of the second catalyst accounts for 0.001-0.1wt% of the polyurethane prepolymer.
10. A method for preparing polyurethane according to claim 8, characterized in that: The second catalyst includes at least one of an organic tin catalyst, an organic amine catalyst, an organic mercury catalyst and an organic bismuth catalyst.
Citation Information
Patent Citations
Method for producing polymer polyols containing secondary hydroxyl terminal group
CN111961196A
Polyester composition for lubricant oil, production thereof and lubricant oil composition
JP1996208814A